Memperkuat Posisi Penataan Ruang Daerah melalui Penciptaan Good Governance - Argo, Teti (Center for Research and Community Services ITB, 2004)
The tradition of establishing spatial arrangement in order to leading the future of human settlement in Indonesia has been decided. Many cities and regencies realize the need ø develop ones in order to direct their settlement. With the introduction of good governance and its principles as a concept to fight against monocratic decision making, leads toward realizing that applying good governance principles that help posit and reshape the spatial attangement and planning in Indonesia. This articles describes conceptually efforts towards linking spatial arrangement and good governance